Investigation of the Effects of the Endogenous Cannabinoid Anandamide on Luminal A Breast Cancer Cell Line MCF-7: Effects of the Endogenous Cannabinoid - Çetin, İdil and Topçul, Mehmet (Cellular and Molecular Biology, 2022)
The present study was carried out to investigate anti-tumoral effects of Anandamide (AEA) in luminal A breast cancer cell line MCF-7. Cell viability was measured by MTT assay and cell index was measured by xCelligence DP analyzer system. The Feulgen method was used to determine the mitotic index parameter, and the 3H-Thymidine method was used to determine the labeling index parameter. The apoptotic index parameter was determined using a fluorescent dye DAPI. The results of this study showed that 25 µM Anandamide concentration was the optimum concentration for MCF-7 cells. While this concentration decreased the proportion of cells in the mitotic phase and synthesis phase, it increased the proportion of apoptotic cells.